MAQASID SYARIAH REVIEW TO PROVISION OF GUARANTEES ON THE DEBT CONTRACTS - azimah, ismatul (Jurnal Ilmiah Pesantren, 2023)
This study aims to determine the implementation of maslahah values for the application of guarantees in debt contracts, because at the initial concept of debt contracts there is no guarantee in providing financing, but in practice there are guarantees that must be given by the customer to the capital provider as the application is strengthened. By the rule of law, for this reason it will be studied in more depth for benefits in the application of guarantees as the aim of maqashid sharia. The method used in this research is literature research which is60 qualitative in nature, data is collected using the documentary method, and descriptive analytical data analysis method. The results of this study indicate that the concept of having a guarantee in a debt contract is maslahah hajiyyah as the category of Imam Al-Syatibi’s thought, so that if it is abolished then it is likely to experience difficulties in the future, but the financing contract is still valid. The author is of the opinion that for the sake of achieving benefit it would be nice if guarantees were given in the form of rahn or kafalah because they are included in the category of protecting assets. Apart from considering the benefit, in muamalah one should not override orders to help each other and stick to a mutual agreement in the contract.